Body weight and statistic vital of Texel sheep in Wonosobo District by giving the ramie hay as an additional woof - AGUS KUNTJORO; SUTARNO SUTARNO; OKID PARAMA ASTIRIN (Nusantara Bioscience, 2009)
Abstract. Kuntjoro A, Sutarno, Astirin OP. 2009. Body weight and statistics vital of Texel sheep in Wonosobo District by giving the ramie hay as an additional woof. Nusantara Bioscience 1: 23-30. This research is aimed to observe the body weight and vital statistic measurement of 50 Texel sheep. Sheep are classified into five treatments of giving woof P0 (giving greenish tree woof without concentrate), P1 (giving greenish woof and concentrate without adding the ramie hay/0%) concentrate), P2 (giving greenish woof and concentrate by adding 10%) ramie hay), P3 (giving greenish woof and concentrate by adding 20%) ramie hay), P4 (giving greenish woof and concentrate by adding 30%) ramie hay), every treatment was repeated 10 times. The result shows that even though it can’t replace the concentrate function, adding ramie hay as much as 10%), 20%) and 30%) on sheep woof can increase the body weight’s growth, respectively 186.67 g/day, 153.34 g/day dan 103.34 g/day. The addition of ramie hay 10%), 20%) and 30%) can increase the addition of statistic vital’s measurement on breast of sheep livestock 1.20 cm); 0.95 cm) and 0.90 cm); the addition of statistic vital measurement on the body length of sheep livestock 0.05 cm); 1.00 cm) and 0.75 cm) and also the addition of breast width is 1.50 cm); 0.15 cm) and 0.3 cm). Meanwhile, the addition of ramie hay on livestock woofs can only increase the addition of vital statistical measurement on the breast at giving 30%) as big as 0.15 cm). It is needed to know further about giving ramie hay by comparing hay of different concentrations of leaf and stems.